Reseña: Three revolutions: Steering automated, shared, and electric vehicles to a better future - Ana Ruiz-Varona (Boletín de la Asociación de Geógrafos Españoles, 2019)
Sperling, Daniel. (2018). Three revolutions: Steering automated, shared, and electric vehicles to a better future. Estados Unidos de América: IslandPress, 234 pp.